Ekspressiv grammatik - Arndt, Hans (HERMES - Journal of Language and Communication in Business, 1989)
The aim of this paper is to consider how to present pedagogical grammar (PG) for advanced students. Taking its point of departure in the lack of structural flexibility often instantiated in student writing, the paper discusses the requirements for an advanced PG, compared to those for theoretical grammar on the one hand and for a beginner's PG on the other. It goes on to outline how an advanced PG can be formulated so as to support and enhance more expressive writing.